THE INFLUENCE OF JOB STRESS AND INCENTIVES EMPLOYEE TURNOVER INTENTION AT YAPIKA GOWA GENERAL HOSPITAL - Muhammad Alias; Mursidah Abu; Hamri Hamri (Journal of Research in Social Science and Humanities, 2024)
Yapika General Hospital Gowa is a public (private) hospital that provides health services in the neighborhood or community of Gowa and its surroundings. According to a pre-survey conducted with several employees of RSU Yapika Gowa, the high turnover intention is due to employees who feel stressed at work and tend to look for new jobs due to employee professionalism at work, which results in high turnover rates. while the application of providing incentives to employees still needs to be improved. Because delays in providing incentives can cause frustration, which can affect very high turnover intentions, The purpose of this study was to determine the effect of work stress on turnover intention at Yapika Gowa General Hospital and to determine the effect of incentives on turnover intention at Yapika Gowa General Hospital. . Based on the level of explanation, this research is classified as causal associative research with a research approach using a quantitative approach. From the results of the analysis conducted on the first hypothesis, it can be concluded that job stress (X1) has a positive and significant effect on turnover intention (Y). This means that there is a significant relationship between job stress and turnover intention. This shows that the higher the level of job stress, the higher the level of turnover intention felt by employees at Yapika Gowa General Hospital. From the results of the analysis carried out on the second hypothesis, it can be concluded that the provision of incentives (X2) has a positive and significant effect on turnover intention (Y). This means that there is a significant relationship between providing incentives and turnover intention. This shows that low compensation can increase the turnover intention rate at Yapika Gowa General Hospital.